2019
DOI: 10.1017/s1047951119000829
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy for prediction of extubation success after neonatal cardiac surgery

Abstract: Introduction:Reliable predictors of extubation readiness are needed and may reduce morbidity related to extubation failure. We aimed to examine the relationship between changes in pre-extubation near-infrared spectroscopy measurements from baseline and extubation outcomes after neonatal cardiac surgery.Materials and Methods:In this retrospective cross-sectional multi-centre study, a secondary analysis of prospectively collected data from neonates who underwent cardiac surgery at seven tertiary-care children’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(41 reference statements)
0
3
0
1
Order By: Relevance
“…The same cardiovascular construct can cause lower arterial oxygenation 10 minutes post-extubation (1-3, 6, 7, 14, 24-26, 30, 31). Other studies also found a reduction in renal NIRS during an extubation readiness trial and an increase in cerebral NIRS from baseline to extubation in congenital heart patients at risk of extubation failure (24,25). However, those studies did not assess speci cally the Norwood population.…”
Section: Discussionmentioning
confidence: 98%
“…The same cardiovascular construct can cause lower arterial oxygenation 10 minutes post-extubation (1-3, 6, 7, 14, 24-26, 30, 31). Other studies also found a reduction in renal NIRS during an extubation readiness trial and an increase in cerebral NIRS from baseline to extubation in congenital heart patients at risk of extubation failure (24,25). However, those studies did not assess speci cally the Norwood population.…”
Section: Discussionmentioning
confidence: 98%
“…Although IDO 2 has previously been used in predicting cardiac arrest (36), this is the first report utilizing the risk analytics algorithms IDO 2 and IVCO 2 to predict extubation failure. Several studies have identified near-infrared spectroscopy (NIRS) as a useful adjunct to ERTs in predicting extubation failure (15, 16). IDO 2 uses NIRS in addition to a number of other physiologic and laboratory values to provide an estimation of inadequate oxygen delivery during weaning and discontinuation of MV.…”
Section: Discussionmentioning
confidence: 99%
“…Previously identified associations with extubation failure among CHD patients include longer MV duration, use of an uncuffed endotracheal tube, and airway anomalies (10, 12, 13). Currently available ERT protocols have primarily been evaluated in noncardiac patients (14) and generally focus on respiratory parameters without factoring in support that MV provides to nonrespiratory organ systems (15, 16). The primary aim of this study was to identify factors associated with extubation failure following cardiac surgery.…”
mentioning
confidence: 99%
“…Las mediciones de NIRS (espectroscopía cercana al infrarrojo) cerebral y somático no fueron estadísticamente diferentes entre los que fueron extubados con éxito y los que fallaron, pero los valores previos a la extubación fueron significativamente más altos en los recién nacidos que se extubaron con éxito. Un aumento de los valores NIRS cerebral en ≥ 5% desde el inicio de la ventilación hasta el momento de la extubación tuvo un valor predictivo positivo para el éxito de la extubación del 98,6% (IC del 95%: 91,1-99,8%) (43). Una disminución en el NIRS somático mínimo de al menos un 10% durante un ensayo de preparación para la extubación tienen una probabilidad 6 veces mayor de fracaso de la extubación (p = 0,02; 95 % IC, 1,26-29,8).…”
Section: ¿Cuál Es La Pauta Más Recomendada Para Preparar Un Paciente ...unclassified